Dinamika Fungsi Ruang di Bale Banjar Titih Denpasar, Bali - Putu Ayu Hening Wagiswari; Nyoman Widya Paramadhyaksa; Gusti Ayu Made Suartika (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2019)
The existence of public space has an important role in city development. In Bali, bale banjar (bale: a hall; banjar: a neighborhood association) is known as a place for various socio-cultural activities. Every member of a banjar is tied up by certain moral values, consensus, codes, and traditions which are all contained in a set of banjar awig-awig (rules). Bale banjar is one of many unique traditions in built form that remains intact in Bali. This article explains the dynamic functions of spaces available in a bale banjar. Two main research problems discussed within are the dynamic functions of spaces in a bale banjar throughout different periods in history and also the determining factors affecting this dynamic. In its process of unveiling both of these phenomenons, this research uses qualitative method with a phenomenology approach and selects Banjar Titih as a case study. The study result finds that the dynamic functions of a bale banjar demonstrate that as times go by, there is a tendency for the bale Banjar Titih to have more complex types and uses of spaces. This is due to mainly to the following factors, including the growing number of the banjar members; the shifting view from that which sees bale banjar as a socio-cultural center of the community into a view that sees bale banjar as a space to bring in financial profits/contribution; and change in people's people way of interactions. To date members of the Banjar Titih cope well with this shift as to how the spaces in their bale banjar have been modified from time to time to suit changes in many determining factors. Keywords: dynamic, functions of space, bale banjar Abstrak Keberadaan ruang publik memiliki peran penting dalam perkembangan sebuah kota dalam mewadahi kegiatan masyarakat. Di Pulau Bali dikenal dengan adanya bale banjar sebagai wadah masyarakat dalam melakukan kegiatan sosio kultural. Setiap kegiatan yang dilakukan oleh warga banjar terikat oleh nilai moral, hukum dan kebudayaan yang diatur dalam awig-awig banjar. Bale banjar merupakan wujud budaya yang telah mempertahankan eksistensi masyarakat Bali hingga saat ini. Artikel ini membahas tentang dinamika fungsi ruang bale banjar. Fokus permasalahan yang diangkat adalah bagaimana proses terjadinya dinamika fungsi ruang bale banjar dari periode awal hingga periode modern serta faktor-faktor yang mempengaruhi. Dalam mengungkap fenomena ini digunakan metode kualitatif dengan pendekatan fenomenologi. Hasil survey lapangan ditemukan bahwa Banjar Titih merupakan salah satu banjar yang mengalami dinamika fungsi ruang. Adapun hasil temuan menunjukkan adanya kecenderungan merubah fungsi ruang bale banjar dari bentuk yang sederhana menjadi modern karena disebabkan oleh faktor pertumbuhan penduduk, faktor ekonomi dan faktor pola pikir masyarakat. Fenomena dinamika fungsi ruang bale Banjar Titih merupakan topik yang menarik untuk diteliti karena relevan dengan dasar ilmu planologi. Warga Banjar Titih mampu mengelola fungsi ruang bersinergi dengan fungi utamanya sebagai ruang publik sehingga dinamika fungsi ruang yang terjadi dapat bermanfaat bagi warga banjar. Kata kunci: dinamika, fungsi ruang, bale banjar